Structural, Magnetic, and Mössbauer Study on Nb and Heat Treatment of Fe-Si-B-P-Cu-Nb Ribbons - Hyunkyung Lee; Hyunkyung Choi; Young Rang Uhm; Haein Choi-Yim (Metals)
This study aims to enhance the amorphous formation ability and magnetic properties that are crucial for the production of high-quality nanocrystalline alloys. The structural, thermal, and magnetic characteristics of the alloy ribbons were analyzed through a systematic adjustment of Nb content, and, including Nb, significantly improved the amorphous formation ability and thermal stability of the alloy, which is vital for nanocrystalline production. By varying the Nb content within Fe85-xSi2B8P4Cu1Nbx (x = 0.0, 0.5, 1.0, and 1.5), we explored finer adjustments to achieve homogeneous amorphousness during the melt spinning process. Careful control over the Nb content facilitated the production of amorphous ribbons with consistent homogeneity, which was critical for the subsequent fabrication of nanocrystalline structures through heat treatment. As a result, the amorphous ribbon of Fe85.5Si2B8P4Cu1Nb0.5 showed a low coercivity of 7 A/m. The heat treatment showed a remarkably high saturation magnetic flux density of 1.94 T. Additionally, the grain size (D) decreased as the Nb content increased, with D values ranging from 25.09 nm to 24.29 nm, as calculated by the Scherrer formula. Mössbauer spectroscopy confirmed the formation of nanocrystalline and residual amorphous phases. The hyperfine magnetic field values (Beff) decreased from 25.7 T to 24.7 T in the amorphous samples and reached 33.0 T in the nanocrystalline phases. This study highlights Nb’s positive impact on thermal stability and amorphous formation capacity in Fe-Si-B-P-Cu alloys, culminating in the successful fabrication of nanocrystalline ribbons with superior structural and magnetic properties.